Different Frontal Involvement in ALS and PLS Revealed by Stroop Event-Related Potentials and Reaction Times - Amato, Ninfa; Riva, Nilo; Cursi, Marco; Martins Silva, Ana; Martinelli, Vittorio; Comola, Mauro; Comi, Giancarlo; Leocani, Letizia (Frontiers in Aging Neuroscience, 2013)
BACKGROUND: A growing body of evidence suggests a link between cognitive and pathological changes in amyotrophic lateral sclerosis (ALS) and in frontotemporal lobar dementia (FTLD). Cognitive deficits have been investigated much less extensively in primary lateral sclerosis (PLS) than in ALS. OBJECTIVE: to investigate bioelectrical activity to Stroop test, assessing frontal function, in ALS, PLS and control groups. METHODS: 32 non-demented ALS patients, 10 non-demented PLS patients and 27 healthy subjects were included. Twenty-nine electroencephalography (EEG) channels with binaural reference were recorded during covert Stroop task performance, involving mental discrimination of the stimuli and not vocal or motor response. Group effects on event related potentials (ERPs) latency were analyzed using statistical multivariate analysis. Topographic analysis was performed using low resolution brain electromagnetic tomography (LORETA). RESULTS: ALS patients committed more errors in the execution of the task but they were not slower, whereas PLS patients did not show reduced accuracy, despite a slowing of reaction times (RTs). The main ERP components were delayed in ALS, but not in PLS, compared with controls. Moreover, RTs speed but not ERP latency correlated with clinical scores. ALS had decreased frontotemporal activity in the P2, P3 and N4 time windows compared to controls. CONCLUSION: These findings suggest a different pattern of psychophysiological involvement in ALS compared with PLS. The former is increasingly recognized to be a multisystems disorder, with a spectrum of executive and behavioural impairments reflecting frontotemporal dysfunction. The latter seems to mainly involve the motor system, with largely spared cognitive functions. Moreover, our results suggest that the covert version of the Stroop task used in the present study, may be useful to assess cognitive state in the very advanced stage of the disease, when other cognitive tasks are not applicable.